JAK/STAT inhibitor therapy partially rescues the lipodystrophic autoimmune phenotype in Clec16a KO mice - Rahul Pandey (Nature Portfolio, 2021)
Abstract CLEC16A is implicated in multiple autoimmune diseases. We generated an inducible whole-body knockout (KO), Clec16a ΔUBC mice to address the role of CLEC16A loss of function. KO mice exhibited loss of adipose tissue and severe weight loss in response to defective autophagic flux and exaggerated endoplasmic reticulum (ER) stress and robust cytokine storm. KO mice were glucose tolerant and displayed a state of systemic inflammation with elevated antibody levels, including IgM, IgA, Ig2b and IgG3, significantly reduced circulating insulin levels in the presence of normal food consumption. Metabolic analysis revealed disturbances in the lipid profile, white adipose decreasing concomitantly with enhanced inflammatory response, and energy wasting. Mechanistically, endoplasmic reticulum (ER) stress triggers excessive hormone sensitive lipases (HSL) mediated lipolysis which contributes to adipose inflammation via activation of JAK-STAT, stress kinases (ERK1/2, P38, JNK), and release of multiple proinflammatory mediators. Treatment with a JAK-STAT inhibitor (tofacitinib) partially rescued the inflammatory lipodystrophic phenotype and improved survival of Clec16a ΔUBC mice by silencing cytokine release and modulating ER stress, lipolysis, mitophagy and autophagy. These results establish a mechanistic link between CLEC16A, lipid metabolism and the immune system perturbations. In summary, our Clec16a ΔUBC mouse model highlights multifaceted roles of Clec16a in normal physiology, including a novel target for weight regulation and mutation-induced pathophysiology.